The Government’s Role in Interfaith Marriage Rights Protection: A Case Study of Adjustment and Social Integration - Rosidah, Zaidah Nur; Karjoko, Lego; Palil, Mohd Rizal (Journal of Human Rights, Culture and Legal System, 2023)
The research aims to determine the government's role in interfaith marriage rights protection in Indonesia and Malaysia. This research belongs to normative research that examines the role of government in the religious difference in marriage in Indonesia and Malaysia. This research employed a case approach, namely the study of the role of government in interfaith marriage rights protection. The techniques of collecting law items were conducted using literature research, while the analysis techniques were performed using deductive syllogism and interpretative methods. The results indicated that interfaith marriages are not technically recognized in Indonesia since the marriage connection is regarded to be a contract between two persons of the same religion.Â  While this is going on, interesting cases frequently take place near the Malaysian and Indonesian borders, particularly in the Sambas region. The Indonesian government's role in intermarriage rights protection is manifested in the Indonesian judiciary. The courts have sanctioned multiple interfaith marriages. Religious conflicts that occur in Malaysia cannot be avoided. It may become a ticking time bomb or a flesh-piercing thorn